PENGARUH BUDAYA ORGANISASI, LINGKUNGAN KERJA DAN KOMPETENSI TERHADAP KINERJA PEGAWAI PADA DINAS ENERGI DAN SUMBER DAYA MINERAL PROVINSI KALIMANTAN SELATAN - rahmat mulyadi (JURNAL KINDAI, 2023)
This study aims to determine and analyze the variables of organizational culture, work environment and competency on employee performance at the Office of Energy and Mineral Resources of South Kalimantan Province simultaneously, partially and dominantly. The research method emphasizes the distribution of questionnaires distributed to 54 respondents. Data analysis techniques to find out the overall picture of the influence of the independent and dependent variables in this study, then carried out with multiple linear regression analysis. The results of the study show the regression equation Y = 6.504 + 0.068.X1 + 0.099.X2 + 0.124.X3 + e. The three hypotheses in this study are proven and accepted that there is a simultaneous, partial and dominant influence on employee performance at the Department of Energy and Mineral Resources of South Kalimantan Province. Keywords: Organizational Culture, Work Environment, Competence, Employee Performance